A Comparison of Agricultural Productivity in the European Union Regions - Natalia Aldaz; Joaquín A. Millán (European Regional Science Association (ERSA), 2003)
This paper is concerned with the estimation of productivity and technical progress based on DEA applied to complete panel data (intertemporal-DEA). Instead of assuming unchanged technology, this paper presents a formulation of technical change that allows the decomposition of productivity scores obtained using intertemporal-DEA. The assumption here is that the technology level in period t for each country is the maximum productivity index obtained until this period. The model assumes that improvements over earlier productivity levels are due to technical progress and that productivity scores below the earlier maximum productivity level are due to inefficiency. The methodology is applied to the analysis of agricultural productivity in the European Union regions in the 1985-97 period. The major source of data is Cronos in Eurostat. This database is used to obtain the disaggregated outputs, intermediate inputs, and depreciation, in current and constant 1990 prices, and labor in annual work units. Capital is measured by depreciation. Land is agricultural area in hectares. Outputs are aggregated in two categories: crops and animal products. Intermediate inputs are grouped into two major categories: feedstuffs and other materials. Aggregation uses national price indices and regional production structures, using the translog price formula. All output, intermediate input and depreciation data, originally reported in local currencies was converted into ECUs, using the 1990 exchange rates. The discriminatory power of the analysis is higher than those with only contemporary analysis of technical efficiency, giving less than 10% of observations in the reference set. Further discrimination is explored using super-efficiency analysis. Radial efficiency measures give only a particular form of inefficiency that can be explained by a proportional contraction in input usage. The paper studies particular output and input efficiencies. As examples, animal products inefficiency is usual only in southern regions. Inefficiency in intermediate consumption usage is pervasive, suggesting the possibility of reducing agricultural production costs. Labor and capital inefficiencies arise in different regions. Land slacks are common in the southern and the westernmost regions.
Keywords: 330